Aeronautical imagination and the figure of the French aviator in the Azorean press (1935/1949) - Faria, Dominique (2020)
In the aftermath of “Atlantic Fever”, several test crews from the most advanced nations in aviation came to the Azores, fighting for the establishment of commercial routes between the Old and the New World. This context explains the 1935 aeronautical mission of the French aviator, Henry Nomy. The analysis of articles in the Azorean newspapers of this period shows the emphasis on the heroic figure of the aviator. In this article, we contrast this aeronautical imaginary with the one prevailing in the Azorean press’ coverage of the accident of the Constellation of Air France, which flew from Paris to New York with a stopover in Santa Maria (Azores) and crashed on the island of São Miguel on October 28, 1949. Studying the articles in these newspapers allows us to grasp a change in the aeronautical imaginary (this time associated with civil aviation): the admiration previously focused on the aviator was now focused on the aircraft itself.